Tinjauan Kuat Lentur Plat Beton Geopolymer Bertulang Dengan Tulangan Bambu Pilin - Saputro, Warseno Bayu; , Ir. Ali Asroni, S.T., M.T (2017)
Geopolymer is an environmentally friendly material that can be developed as an alternative to cement. Geopolymer contains many of the elements silicon and aluminum. These elements are found in many industrial waste materials such as fly ash (fly ash). Geopolymer concrete need for additional alkaline activator binding material in the form of sodium silicate and sodium hydroxide in the ratio of 5: 2. This study aims to apply geopolymer concrete into reinforced concrete structures. In this study made of reinforced concrete plate, the plate dimensions 8 mm x 50 cm x 100 cm. Reinforcement using steel plate D8 and D8 gyre bamboo .. geopolymer concrete mix design refers to previous studies, and normal concrete using the method of ACI with a compressive strength of 20 MPa plan. Number of test specimens of normal concrete cylinders 3, 3 cylinder geopolymer concrete, normal concrete slab reinforcement 3 D8, 3 normal concrete slab reinforcement stranded bamboo D8, 3 geopolymer concrete slab reinforcement D8, and 3 geopolymer concrete slab reinforcement stranded bamboo D8. test results normal concrete density 2.176 g / cm3, while the density of concrete geoplymer greater than normal concrete is 2,259 gr / cm3. The results showed that the quality of normal concrete and reinforcement D8 is still above the 2 geopolymer concrete and bamboo reinforcement gyre D8. The average compressive strength of normal concrete is 19,250 MPa, a little less of the planning that is 20 MPa. Geopolymer concrete compressive strength only reached 12.544 MPa. Maximum bending moment reinforced concrete plate normally D8 of 3.952 kNm., normal concrete slab of reinforced bamboo gyre of 1,860 kNm. D8, D8 reinforced geopolymer concrete slab at 2,100 kNm. and bamboo reinforced geopolymer concrete slab D8 amounting to 1,537 kNm.